RITUALS OF JEKNEK SAPPARA CULTURE (BATH OF SAFAR) IN THE VILLAGE OF BARANGLOE, DISTRICT TAROANG, JENEPONTO REGENCY: A SEMIOTIC ANALYSIS - Nurul Fitrah Yani (Hasanuddin University, 2018)
Thisqualitative descriptive study semiotically discusses the forms –word, phrase and sentence - and meanings of symbols in the ritual of